Exploring the impact of Dy2O3 nanoparticles on the physical characteristics of poly(lactic acid) and polyhydroxyalkanoate composites - KOK, Mediha; Mohammed, Kathrin Sleman; Oner, Ecem Ozen; Qader, Ibrahim Nazem; Aydogdu, Yildirim (Springer, 2025)
Researchers are trying to expand the efficiency and application of shape memory polymers by investigating different parameters on the matrix and additives. This study aims to enhance the physical characteristics by examining the addition of 5%, 10, 20, 30, and 40 wt.% metal oxide Dy2O3 nanoparticles into blended poly(lactic acid) (PLA)/polyhydroxyalkanoate (PHA) polymer. The degree of crystallinity, chemical structure, thermal characteristics, magnetic behavior, surface morphology, and mechanical characterizations were studied using XRD, FTIR, DSC, TGA, VSM, SEM, and tensile test. This study identified that the use of Dy2O3 nanoparticles in the blend increased the glass transition and melting temperatures, while the enthalpy changes and specific heat capacity of the polymer nanocomposite stayed almost constant. The presence of new interfaces between Dy2O3 and the polymer chains was confirmed by FTIR analysis, and the dispersion of the NPs in the polymer matrix was confirmed by SEM analysis. TGA findings proved the enhancement of thermal stability with mass loss of less than 10% at temperatures below 150 degrees C. Moreover, the magnetization vs magnetic strength exhibited the paramagnetic behavior of the blend and nanocomposites where the response to the external magnetic field has a direct correlation with the quantity of the additive nanoparticles in the polymer blend. The same improvement has been detected in the mechanical behavior. The elastic modulus of the nanocomposite increased and the samples with more embedded NPs recorded a higher maximum stress. The presence of Dy2O3 nanoparticles in PLA/PHA blends impacts the thermal and magnetic properties of the nanocomposite.
Keywords: PLA; PHA; Dy2O3 NPs; Thermal analysis; Magnetic behavior